Effect of caffeine on the cardiovascular system and performance: A systematic review - Radomir Pržulj; Oliver Radenkovic; Milan Zelenović; Bojan Bjelıca; Nikola Aksovıć (Turkish Journal of Kinesiology, 2023)
Caffeine is a compound found in the leaves, seeds and fruits of plants such as coffee and guarana. The aim of the systematic review was to determine the influence of caffeine on cardiorespiratory functions and physical performance. The method was the collection of relevant literature in the period from 2011-2022, and their analysis. The results clearly show the benefit and positive influence of caffeine on both investigated areas. The recommended consumption of caffeine should be higher than 75mg in order to expect positive changes and effects. Also, doses above 600mg should not be exceeded due to side effects, especially on the heart. It is necessary to consume caffeine for at least 45 minutes before the planned activity to ensure complete absorption. Caffeine is a very powerful supplement, it is only necessary to take care of the method and amount of dosage.